Digital platforms in partial exams: a point of academic hegemony. As plataformas digitais nas provas parciais: um ponto de hegemonia acadêmica. Les plateformes numériques dans les examens partiels: un point d’hégémonie académique (Ingeniería, Sostenibilidad y Sociedad, 2025)
The purpose of this research is to demonstrate that digital platforms have become an essential tool for conducting midterm exams in higher education. Among the identified benefits are the flexibility in categorizing and systematizing exams, the ability to use multimedia resources and applications, and the ease of immediately applying certain grading processes. However, it is important and necessary to highlight concerns regarding academic integrity, unequal access to technology, the need for some workshops to remain in-person, and the preparation of teachers to face the challenge of digital platform assessments.The study concludes that it is necessary to strengthen digital competencies, create and maintain supervision mechanisms, and redesign evaluation strategies to focus on critical thinking and knowledge application rather than simple content memorization. Furthermore, it emphasizes the importance of ensuring student equity to eliminate current technological gaps.